2009
DOI: 10.1002/syn.20734
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and extrastriatal dopamine release measured with PET and [18F] fallypride

Abstract: The amphetamine challenge, in which PET or SPECT radioligand binding following administration of amphetamine is compared to baseline values, has been successfully used in a number of brain imaging studies as an indicator of dopaminergic function, particularly in the striatum. [ 18 F] fallypride is the first PET radioligand that allows measurement of the effects of amphetamine on D 2 /D 3 ligand binding in striatum and extra-striatal brain regions in a single scanning session following amphetamine. We scanned 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 54 publications
8
87
0
Order By: Relevance
“…Fourth, the suitability of labelled fallypride to detect a DA signal in the cortex has been questioned, specifically in response to an amphetamine challenge. 62,63 A low signal-to-noise ratio in extrastriatal regions, combined with high intersubject variability, have likely prevented reaching statistically significant drug-induced binding decreases, though with percent displacement above normal test-retest variations 14,31 and previous successful reports. 13,14 In the present study, the sensitivity of the method may have been increased by using a higher-resolution PET scanner (HRRT), fallypride labelled with 18 F instead of 11 C, the lower intersubject variability, the nonpharmacological challenge used, and the behaviour-based division of subgroups.…”
Section: Limitationsmentioning
confidence: 99%
“…Fourth, the suitability of labelled fallypride to detect a DA signal in the cortex has been questioned, specifically in response to an amphetamine challenge. 62,63 A low signal-to-noise ratio in extrastriatal regions, combined with high intersubject variability, have likely prevented reaching statistically significant drug-induced binding decreases, though with percent displacement above normal test-retest variations 14,31 and previous successful reports. 13,14 In the present study, the sensitivity of the method may have been increased by using a higher-resolution PET scanner (HRRT), fallypride labelled with 18 F instead of 11 C, the lower intersubject variability, the nonpharmacological challenge used, and the behaviour-based division of subgroups.…”
Section: Limitationsmentioning
confidence: 99%
“…A more recently developed tracer, though, [ 18 F]fallypride, has higher affinity than [ 11 C]raclopride for D2/D3 receptors enabling the measurement of DA release in regions where the concentration of DA receptors is substantially lower than striatum (Mukherjee et al, 2002;Slifstein et al, 2010). In the present study, we used this tracer with high-resolution PET to assess the ability of drug cues to induce DA release in the amygdala, hippocampus, and striatum of volunteers meeting diagnostic criteria for cocaine dependence.…”
Section: Introductionmentioning
confidence: 99%
“…To rule out possible confounds, we tested whether BPnd in the identified vmPFC cluster remained predictive after controlling for PET scanner type and timing differences (length of overall placebo PET acquisition time; see Methods, Table S1), peak plasma-amphetamine level, effective dAMPH dose, sex, and subject age. After controlling for these variables, there was (Cropley et al, 2008;Riccardi et al, 2006a;Slifstein et al, 2010), we identified a large cluster (k=4,874) comprised of bilateral striatum that also encompassed the midbrain that displayed significant DA release ( Figure S1) in addition to areas in the temporal cortices and bilateral insula (Table S3).…”
Section: Baseline Drd2/3 Availability and Deq Ratings: Relationship Bmentioning
confidence: 99%
“…Until now, work focused on assessing a potential relationship between extrastriatal DA characteristics and subjective responses has been limited due to 11 Craclopride and 123 I-IBZM's inability to reliably estimate DRD2/3 availability (measured as binding potential, BPnd) outside the striatum. The radiotracer 18 F-fallypride, however, is able to estimate DRD2/3 BPnd in PFC, temporal lobes, and the insula in addition to the striatum (Mukherjee et al, 2002;Riccardi et al, 2008) and can index DA release after damphetamine (dAMPH) administration, measured as %ΔBPnd from baseline (Riccardi et al, 2006a;Slifstein et al, 2010). We were particularly interested in using fallypride to test whether DA functions in paralimbic cortical areas, specifically the mPFC/OFC, related to subjective responses to dAMPH given past evidence that activity in these areas are increased in response to psychostimulants in drug naïve individuals (Vollm et al, 2004) and correlate with their self-reported euphoric effects (Udo de Haes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%